Fan pilgrimage and Thai genre films: play, space and the search for vernacular cultural sites. Issue 3 (3rd July 2021) - Promkhuntong, Wikanda
ABSTRACT: This paper extends the notion of film tourism in the context of Thailand from the focus on destination marketing to affective connections between film locations and fans. Combining frameworks from fan studies particularly the notion of pilgrimage, and a conceptual way of linking play with space in game and architectural studies, the paper examines playful practices at film locations and associated spaces mediated by digital photography, video and online story-telling associated with the Thai genre films called nang rak, which emerged in the early 2000s–2010s. The examination of play practices highlights the imaginative, performative and mediated plays by film fans, which created play movements in space or 'kinesis' at the film locations making them become cultural playgrounds for identity negotiations and the sites for expressing desires for affective cities. The paper also invites further consideration on fan pilgrimage in relation to changes with political climate, tourism development and vernacular cultural sites.